High prevalence of abdominal aortic aneurysm in older men with cerebrovascular disease: Evaluation of a local screening program - Loban, M.; Gratama, J. W. C.; Klemm, P. L.; Van Leeuwen, Roeland B.; Vriesema, H.; Bienfait, Henri Paul (Frontiers in Neurology, 2023)
Introduction Patients with cerebrovascular disease may suffer from other vascular morbidities, such as abdominal aortic aneurysm (AAA). Previously, a high prevalence of AAA has been demonstrated in men 60 years of age and older who have experienced TIA or stroke. This report evaluates the results of a decade's operation of a local screening program for AAA in this selected neurologic population. Methods Men aged ≥60 years and admitted to the neurology ward of a community-based hospital in the Netherlands from 2006 to 2017 with a diagnosis of TIA or stroke were selected for screening. The diameter of the abdominal aorta was assessed by abdominal ultrasonography. Patients with detected AAA were referred for evaluation by a vascular surgeon. Results AAA was detected in 72 of 1,035 screened patients (6.9%). AAAs with a diameter of 3.0–3.9 cm accounted for 61.1% of the total aneurysms found; AAAs with a diameter of 4.0–5.4 cm accounted for 20.8% of the total; and large aneurysms with a diameter of ≥5.5 cm accounted for 18.1% of all aneurysms discovered. A total of 18 patients (1.7%) underwent elective aneurysm repair. Discussion The detection rate of AAA in older men with cerebrovascular disease was roughly 5-fold the detection rate in known European screening programs in older men from the general population. The proportion of large AAAs (≥5.5 cm) was also substantially higher. These findings reveal a previously unknown co-morbidity in patients with cerebrovascular disease and may be helpful for cardiovascular management of this large group of neurologic patients. Current and future AAA screening programs may also benefit from this knowledge.